Analisis Cemaran Logam Berat Tembaga (Cu) pada Ikan Tembang (Sardinella gibbosa) yang dipasarkan di Makassar - Nurham, .; Andi, Mu’nisa (bionature, 2010)
analysis of heavy metals such as copper (Cu) in Sardinella gibbosa has been which marketed in Makassar. Fish samples were collected from TPI Lelong and TPI Rajawali. Cu levels were determined by atonomic absorption spectrophotometry (AAS). The analyses showed estimated of 0.0189 mg/kg (TPI Lelong) and 0.0144 mg/kg (TPI Rajawali) levels of Cu in fish. It was then concluded that the levels of Cu were still below threshold.Â